Stokesosauridae clade nov., a new family name for a branch of basal tyrannosauroids - Yun, Chan-Gyu; Carr, Thomas D. (Zootaxa, 2020)
The majority of tyrannosauroid phylogenies published in the last 10 years have recovered a clade of basal tyrannosauroids that include Stokesosaurus clevelandi Madsen, 1974, Eotyrannus lengi Hutt et al., 2001 and Juratyrant langhami (Benson, 2008), which is positioned between Dilong Xu et al., 2004 and more derived tyrannosauroids such as Xiongguanlong Li et al., 2010 (e.g., Brusatte et al., 2010, 2011; Brusatte and Benson, 2013; Lü et al., 2014; Brusatte and Carr, 2016; Yun, 2016; Carr et al., 2017; Delcourt and Grillo, 2018; Nesbitt et al., 2019; Zanno et al., 2019; Wu et al., 2020). Carr et al. (2017) first called this clade as “Stokesosauridae”, but did not define or diagnose this clade; but later the name was adopted and  used as valid by Wu et al. (2020).